Dispersed Are We: The Novel of Worlds and the World of the Novel in Virginia Woolf’s Between the Acts - Lecercle, Jean-Jacques (Filozofski vestnik, 2022)
Drawing on a forthcoming book by Rok Benčin on the concept of world (the multiplicity of real worlds as transcendental frameworks and the fictional structure thereof), the article proposes a reading of Between the Acts by Virginia Woolf that focuses on the dialectic of dispersion and unity. The novel presents a multiplicity of dispersed and fragmented transcendental frameworks that tend towards – an attempt that is always doomed to fail, but always begins anew – unification within the ideological apparatuses (family, religion, national history, literary canon). In this endless dialectic, literature occupies a singular place, for the fictional structure of these frameworks makes of it a transcendental-abyss, which enables passage from the novel of worlds to the world of the novel.